Contract and domination - Pateman, Carole; Mills, Charles W. (Polity, 2007)
« Contract and Domination offers a bold challenge to contemporary contract theory, arguing that it should either be fundamentally rethought or abandoned altogether. Since the publication of John Rawls's A Theory of Justice, contract theory has once again become central to the Western political tradition. But gender justice is neglected and racial justice almost completely ignored. Carole Pateman's and Charles Mills's earlier books, The Sexual Contract (1988) and The Racial Contract (1997), offered devastating critiques of gender and racial domination and the contemporary contract tradition's silence on them. Both books have become classics of revisionist radical democratic political theory. Now Pateman and Mills are collaborating for the first time in an interdisciplinary volume, drawing on their insights from political science and philosophy. They are building on but going beyond their earlier work to bring the sexual and racial contracts together. In Contract and Domination, Pateman and Mills discuss their differences about contract theory and whether it has a useful future; excavate the (white) settler contract that created new civil societies in North America and Australia; argue via a "non-ideal" contract for reparations to black Americans; confront the evasions of contemporary contract theorists; explore the intersections of gender and race and the global sexual-racial contract; and reply to their critics. »–Page 4 de la couverture.
Section: ix, 306 pages ; 24 cm.
Keywords: approches et analyses; capitalisme; com5170; contrat social; cours; discipline; histoire et politique; intersectionnalité; patriarcat; philosophie; philosophie politique; pol4212; premier cycle; racisme; rapports de domination; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

Femmes, genre, féminisme - Trat, Josette (Éd. Syllepse, 2007)
"Le retour sur l'histoire du courant féministe "lutte de classes" met en évidence l'urgence à penser les rapports sociaux de sexe en les articulant aux rapports de classe et aux rapports Nord-Sud. Quels sont les apports et les limites du Queer pour penser le genre et les oppressions? Quels sont les rapports entre les mouvements féministes et les mouvements gais et lesbiens? Quels sont les effets de la mondialisation néolibérale sur l'oppression des femmes et sur leurs luttes à l'échelle mondiale? Les questions des rapports de classe et celle du racisme ont été également remises au-devant de la scène par la révolte des banlieues dont les filles semblaient toutefois singulièrement absentes. Pourtant, elles luttent contre le sexisme, ainsi que le montre le collectif Féminin-Masculin de Vitry. A l'heure où les retours en arrière sont toujours possibles, comme en atteste l'émergence d'un mouvement masculiniste, la construction d'un courant féministe se donnant pour objectif de changer radicalement la société reste nécessaire pour gagner l'égalité réelle entre hommes et femmes."
Section: 1 v. (120 p.) ; 17 cm
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; histoire et politique; intersectionnalité; militance; premier cycle; queer; rapports de classe; rapports sociaux de sexe; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques